The Role of Economic Digitalization on Portfolio Investment - Firmansyah, Muhammad; Boedirochminarni, Arfida; Yuli, Sri Budi Cantika; Flejterski, Stanislaw (Jurnal Ilmu Ekonomi Terapan, 2025)
Objective: Portfolio investment plays an important role in supporting economic growth, especially with the advancement of technology that facilitates access to information and financial transactions. This study analyzes the impact of internet users, fintech, cashless transactions, and e-commerce on portfolio investment in Indonesia. Design/Methods/Approach: This type of research is quantitative research using secondary data sourced from the Central Bureau of Statistics, Financial Services Authority (OJK), Bank Indonesia, and the Indonesian Economic and Financial Statistics. The research objects used in this study include 34 provinces in Indonesia. The data analysis method in this study uses Vector Autoregression (VAR). This analysis method consists of several tests, including the stationary test, optimum lag test, Granger causality test, Impulse Response Function (IRF), and Forecast Error Variance Decomposition (FEVD). Findings: The study results show that the four variables affect portfolio investment with varying significance levels. Internet users increase access to financial markets and investment opportunities. Fintech provides efficient digital financial services, cashless transactions offer convenience in financial management, and e-commerce creates profitable investment opportunities. Originality/Value: Unlike prior research that examined these factors in isolation, our approach provides a comprehensive understanding by integrating four variables of digitalization into a single framework for analyzing how digital transformation shapes investment behavior. Using a Vector Autoregression (VAR) method with provincial-level data from Indonesia, the study offers novel empirical evidence on the dynamic interplay between digitalization and financial markets in an emerging economy. Practical/Policy implication: The findings highlight the importance of expanding digital infrastructure, enhancing financial literacy, and strengthening regulatory frameworks to foster inclusive and secure digital investment ecosystems. Policymakers and monetary authorities can apply these insights to design policies that promote fintech innovation, ensure transaction security, and improve investor protection.